2017
DOI: 10.1680/jwama.15.00035
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive reservoir rule curves by optimisation and simulation

Abstract: Effective reservoir operation is achieved using suitable rule curves to control the release of water following the release criteria. Conditional cuckoo search (CCS) algorithms and conditional particle swarm optimisation (CPSO) were linked with a reservoir simulation model to identify adaptive optimal reservoir rule curves. Three cases (normal, dry and wet years) were considered when producing the rule curves depending on the inflow pattern and inflow period. Lampao reservoir in Thailand was used to illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The results demonstrated that the shape of new historic rule curve in every cases were homologous to the existing. The characteristics of these new historic rule curves are similar to the optimal rule curves of the reservoirs in Thailand that were previously studied (Ashofteh et al., 2015; Kangrang et al., 2017), mainly due to the effects of seasonal inflow changes.
Fig. 7Optimal historic rule curves of Ubolrat Reservoir using minimize water shortage and minimize excess spill water with CTSA model.
Fig.
…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The results demonstrated that the shape of new historic rule curve in every cases were homologous to the existing. The characteristics of these new historic rule curves are similar to the optimal rule curves of the reservoirs in Thailand that were previously studied (Ashofteh et al., 2015; Kangrang et al., 2017), mainly due to the effects of seasonal inflow changes.
Fig. 7Optimal historic rule curves of Ubolrat Reservoir using minimize water shortage and minimize excess spill water with CTSA model.
Fig.
…”
Section: Resultssupporting
confidence: 55%
“…It can be concluded that the proposed CTSA model is another search suitable technique, so the outcomes are close to optimal goal of the CGA model depend on the identical condition. Nevertheless, the ability of each method was determined by many researches (Bozorg-Haddad et al., 2015; Ming et al., 2015; Kangrang et al., 2017). Include connecting to the multi-condition allowing the reservoir to be managed properly and with the highest efficiency regardless of any situation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of applied the CS to reservoir optimization is indicated in Table 10. Kangrang et al (2017) published a paper dealing with the application of the CS to reservoir optimization. The conditional cuckoo search (CCS) was applied to derive rule curves for a single reservoir in Thailand.…”
Section: Algorithmsmentioning
confidence: 99%
“…The conditional cuckoo search (CCS) was applied to derive rule curves for a single reservoir in Thailand. Kangrang et al (2017) showed that the CCS is efficient in calculating adaptive rule curves under variable inflows. Ming et al (2015) employed the CS to maximize the power generation of a multi-reservoir system in China.…”
Section: Cuckoo Search (Cs)mentioning
confidence: 99%